On the Performance and Isolation of Asymmetric Microkernel Design for Lightweight Manycores - Penna, Pedro H.; Souto, João; Lima, Davidson F. G.; Castro, Márcio; Broquedis, François; Freitas, Henrique C.; Méhaut , Jean-François (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
Multikernel operating systems (OSs) were introduced to match the architectural characteristics of lightweight manycores. While several multikernel OS designs are possible, in this work we argue on one that is structured in asymmetric microkernel instances. We deliver an open-source implementation of an OS kernel with these characteristics, and we provide a comprehensive assessment using a representative benchmark suite. Our results show that an asymmetric microkernel design is scalable and introduces at most 0.9% of performance interference in an application execution. Also, our results unveil co-design aspects between an OS kernel and the architecture of lightweight manycore, concerning the memory system and core grouping.